Malay proverbs in inquisitive Semantics approach lens: The case of Malaysian textbooks - Mohd Ridzuan Md Nasir; Mary Fatimah Subet (Indonesian Journal of Applied Linguistics, 2023)
With reference to the Malay Language Secondary School Standard Curriculum, proverbs in Malaysian contexts are one of the language aspects that students needs to use integrated in the language teaching. This research identified proverbs in the Malaysian secondary school textbooks analyzed using inquisitive semantic approach. The proverbs data were obtained Form 4 and Form 5 Malay Language textbooks, from Ministry of Education Malaysia. Nine pieces of data were identified using the inquisitive semantics study framework involving three stages; surface meaning analysis, the semantics resonance analysis involving speaker’s cognitive by applying the Cross-reference Framework (Kempson, 1986) in the Relevance Theory (Sperber Wilson, 2986; 1995), and the meaning analysis using the inquisitive semantics approach (Jalaluddin, 2014). The study indicated the proverb meaning analysis starting from the knowledge of the meaning from the dictionary, followed by the meaning of the proverbs in the context of sentences, and the exploration into the philosophy and common sense underlying the formation of the proverbs. The study proposed that the textbooks stimulated students’ higher-order thinking skills with the inquiry method to create new discovery and knowledge. In conclusion, the textbooks offered teachers the proverbs analyzed by the inquisitive semantics approach as a teaching approach such to make the process of learning language in their classrooms more meaningful.